Improved Chirp Scaling Algorithm for Processing Squinted Mode Synthetic Aperture Sonar Data - Fan, Naiqiang; Wang, Yingmin; Lv, Yarong (Cybernetics and information technologies : CIT, 2016)
The conventional Chirp Scaling Algorithm is mainly used in side looking or small squint angle mode of synthetic aperture imaging. In application of synthetic sonar, the large squint angle imaging is often required and the range-azimuth coupling is serious. On the basis of studying the principle of the conventional Chirp Scaling Algorithm, we improved the imaging algorithm in large squint mode. We analysed the structure of the echo frequency spectrum and the compensation of phase factor. The improved imaging algorithm designs a more precision of phase compensation factor, and eliminates the high order degree of range and azimuth coupling in the specific mapping band. Any target point is simulated in imaging region by using the improved algorithm. The simulation conclusion showed that the improved Chirp Scaling Algorithm is able to meet the imaging focus and is more suitable to slant imaging as compared with the traditional algorithm.